Kontribusi Sektor Pertanian Pada Pertumbuhan Ekonomi di Provinsi Sulawesi Barat - Imas Wildan Rafiqah; Wydhi Santoso; Sugiyanto Sugiyanto (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2023)
Developing the agricultural sector is one of the key strategies to stimulateeconomic growth in the coming time. The purpose of this study is to knowhowtheagricultural sector contributes and to what extent the agricultural sector contributes toeconomic growth. The analytical method used in this study is the Location Quotient (LQ) using PDRB data from West Sulawesi Province. The results showed that West Sulawesi's agricultural sector contributed the most among other sectors at 38.93%. Theaverage LQ value for the SulBar agricultural sector from 2017-2021 is 2.97. Thismeans that the agricultural sector is the base or leading sector in West Sulawesi because the LQ value is > 1. In the agricultural sector, the sub-sector that has avalue > 1 is the plantation subsector, which is equal to 1.35. This shows that theplantation subsector is a leading sector that makes a major contribution to economicgrowth in West Sulawesi Province